Quantum mechanism of light energy propagation through an avian retina - Zueva, Lidia (2020)
Taking into account the ultrastructure of the Pied Flycatcher foveal retina reported earlier and the earlier reported properties of Muller cell (MC) intermediate filaments (IFs) isolated from vertebrate retina, we proposed a quantum mechanism (QM) of light energy transfer from the inner limiting membrane level to visual pigments in the photoreceptor cells. This mechanism involves electronic excitation energy transfer in a donor-acceptor system, with the IFs excited by photons acting as energy donors, and visual pigments in the photoreceptor cells acting as energy acceptors. It was shown earlier that IFs with diameter 10 nm and length 117 mu m isolated from vertebrate eye retina demonstrate properties of light energy guide, where exciton propagates along such IFs from MC endfeet area to photoreceptor cell area. The energy is mostly transferred via the contact exchange quantum mechanism. Our estimates demonstrate that energy transfer efficiencies in such systems may exceed 80-90%. Thus, the presently developed quantum mechanism of light energy transfer in the inverted retina complements the generally accepted classic optical mechanism and the mechanism whereby Muller cells transmit light like optical fibers. The proposed QM of light energy transfer in the inverted retina explains the high image contrast achieved in photopic conditions by an avian eye, being probably also active in other vertebrates.